Thermal Characteristics of Trapezoidal Overhead Conductors Exposed to Galvanic Corrosion - Mohamad Izzat Nawawi; Shahnurriman Abdul Rahman; Muhammad Mokhzaini Azizan; Konstantinos Kopsidas (Akademia Baru Publishing, 2026)
Indexed by Scopus/MyCite